Incidencia del gasto público en salud en la desnutrición en América Latina y África Subsahariana durante 2000-2016, utilizando técnicas de datos de panel” - Calva Merino, Jessica Selena (2020)
the objective of this research is to examine the incidence of public health expenditure on the variation of undernourishment in Latin America and Sub-Saharan Africa during 2000- 2016. For this purpose, the data was collected from the World Development Indicators (2018), Human Development Index (2018) and the Index of Economic Freedom (2018). The research is based on empirical evidence, as well as Mushkin's (1962) arguments. For the development of the model I used panel data and the generalized least squares (GLS) technique. The main results show the existence of a significant negative relationship between undernourishment and public spending on health in Latin America; while in Sub-Saharan Africa there is a non- significant positive relationship. Within socioeconomic factors that influence undernourishment, it was found that the rural population has a positive and significant relationship in the two regions; Furthermore, it was determined that unemployment and remittances have a positive and significant relationship with undernourishment only in Latin America. On the other hand, education and remittances were found to have a negative and significant relationship with undernourishment in Sub-Saharan Africa. One of the recommended policy implications is that undernourishment is treated as a major problem, ensuring primary health care for the entire population with specific interventions, so that they achieve a noticeable and permanent impact over time and do not occur. romps in the fight to eradicate it.